Metal-embedded SU-8 Slab Techniques for Low-resistance Micromachined Inductors - Manot Mapato; Prapong Klysuban; Thanatchai Kulworawanichpong; Nimit Chomnawang (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This work presents a new fabrication technique for micro power inductors by using metal-embedded SU-8 slab molding techniques. The proposed technique uses X-ray lithography to fabricate high-aspect-ratio LIGA-like microstructures in form of embedded structures in the SU-8 slab. This process was applied to fabricate an inductor’s windings with an aspect ratio of 10, which can provide very low resistance but still preserve a small form factor and low profile. Inductors were designed as pot-core structures with overall heights of 370 μm and embedded with 250-μm-thick windings. From the advantage of metal embedded SU-8 slab techniques, 8 μm-thick permalloy core could be fabricated by electroplating around the winding in a single step that could help simplify the process. Four types of inductors were fabricated with 3, 5, 10, and 16 turns in the area of 1.8 to 9.5 mm2. The measured inductance was in the range of 70 nH to 1.3 μH at 1 MHz and DC resistance of 30–336 mΩ for 3–16 turns, respectively. The DC resistance of fabricated inductor was low, as expected, and showed good result compared with the results in literature.